Defining civilisation and religion - Akhmetova, Elmira (International Institute of Advanced Islamic Studies, 2008)
This essay is an attempt to study definitions of Civilisation, the main forces behind historical progress as well as the role of man and religion in establishing societies from an Islamic perspective by highlighting ideas of the Muslim scholars Ibn Khaldun, Shah Wali Allah, Said Nursi and Malik Bennabi. It also underlines some fundamental differences between modern and Islamic approaches in studying history and civilisation, and suggests that modern methods of studying social sciences should be urgently revised.